Viewable wildlife species along Sungai Haji Kuning in Sebatik Island, Sabah - Lim, Wing-Shen; Nurliza Hasmat; Andy Russel Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2019)
Preliminary assessment was conducted to determine wildlife species that could be sighted along Sungai Haji Kuning in Sebatik Island. Opportunistic sampling was conducted along Sungai Haji Kuning at August 6, 2018, through boat survey. Nine wildlife species were encountered within midstream and downstream regions, in which Long-tailed Macaque was encountered most frequently, followed by Brahminy Kite and the endangered Proboscis Monkey. The near-threatened Oriental Darter, vulnerable Bearded Pig and migratory Chinese Egret were viewable along this river as well. Shannon and Simpson Diversity Indices obtained in present study indicated that this riverine habitat housed rich and evenly-distributed wildlife diversity. Hence, riverine mangrove of Sungai Haji Kuning is important to the survival of both resident and migratory wildlife species, and then high viewing success of proboscis monkey for a long duration further emphasizes its potential for future river-cruising wildlife-watching opportunity.